The Transcription Factor Lrp of Pantoea stewartii subsp. stewartii Controls Capsule Production, Motility, and Virulence Important for in planta Growth - Bartholomew, Holly P.; Reynoso, Guadalupe; Thomas, Brandi J.; Mullins, Chase M.; Smith, Chastyn; Gentzel, Irene N.; Giese, Laura A.; Mackey, David; Stevens, Ann M. (Frontiers in Microbiology, 2022)
The bacterial phytopathogen Pantoea stewartii subsp. stewartii causes leaf blight and Stewart’s wilt disease in susceptible corn varieties. A previous RNA-Seq study examined P. stewartii gene expression patterns during late-stage infection in the xylem, while a Tn-Seq study using a P. stewartii mutant library revealed genes essential for colonization of the xylem. Based on these findings, strains with in-frame chromosomal deletions in the genes encoding seven transcription factors (NsrR, IscR, Nac, Lrp, DSJ_00125, DSJ_03645, and DSJ_18135) and the one hypothetical protein (DSJ_21690) were constructed to further evaluate the role of the encoded gene products during in vitro and in planta growth. Assays for capsule production and motility indicate that Lrp plays a role in regulating these two key physiological outputs in vitro. Single infections of each deletion strain into the xylem of corn seedlings determined that Lrp plays a significant role in P. stewartii virulence. In planta xylem competition assays, between co-inoculated deletion and the corresponding complementation or wild-type strains, as well as in vitro growth curves, determined that Lrp controls functions important for P. stewartii colonization and growth in corn plants, whereas IscR may have a more generalized impact on growth. Defining the role of essential transcription factors, such as Lrp, during in planta growth will enable modeling of key components of the P. stewartii regulatory network utilized during growth in corn plants.